Analytical Surveys of Stonehenge and its Immediate Environs, 2009–2013: Part 1 – the Landscape and Earthworks. (14th August 2014) - Field, David; Linford, Neil; Barber, Martyn; Anderson-Whymark, Hugo; Bowden, Mark; Topping, Peter; Linford, Paul; Abbott, Marcus; Bryan, Paul; Cunliffe, Deborah; Hardie, Caroline; Martin, Louise; et al.
Abstract : Integrated non-invasive survey in the Stonehenge 'triangle', Amesbury, Wiltshire, has highlighted a number of features that have a significant bearing on the interpretation of the site. Among them are periglacial and natural topographical structures, including a chalk mound that may have influenced site development. Some geophysical anomalies are similar to the post-holes in the car park of known Mesolithic date, while others beneath the barrows to the west may point to activity contemporary with Stonehenge itself. Evidence that the 'North Barrow' may be earlier in the accepted sequence is presented and the difference between the eastern and western parts of the enclosure ditch highlighted, while new data relating to the Y and Z Holes and to the presence of internal banks that mirror their respective circuits is also outlined. RÉSUMÉ: Prospections analytiques de Stonehenge et de ses environs immédiats, 2009–2013: Partie 1 – paysage et fortifications, de David Field, Neil Linford, Martyn Barber, Hugo Anderson-Whymark, Mark Bowden, Peter Topping et Paul Linford Une prospection intégrée, non invasive du 'triangle' de Stonehenge, à Amesbury, Wiltshire, a souligné un certain nombre de traits qui ont une portée considérable sur l'interprétation du site. Parmi eux se trouvent des structures topographiques pré-glaciaires et naturelles, y compris un tertre de craie qui pourrait avoir eu une influence sur le développement du site. Des anomalies géophysiques ressemblent aux trous de poteaux du parking dont on connait la date mésolithique tandis que d'autres, sous les tertres funéraires à l'ouest, pourraient indiquer une activité contemporaine de Stonehenge lui-même. Des témoignages que le Tertre Funéraire Nord pourrait être plus ancien que dans la séquence admise actuellement sont présentés et la différence entre les parties est et ouest du fossé de l'enclos est mise en évidence, tandis que de nouvelles données au sujet des Trous Y et Z et de la présence de talus internes calqués sur leurs circuits respectifs sont aussi résumées. ZUSSAMENFASSUNG: Analytische Surveys von Stonehenge und seiner unmittelbaren Umgebung 2009-2013: Teil 1 – Die Landschaft und die Erdwerke, von David Field, Neil Linford, Martyn Barber, Hugo Anderson-Whymark, Mark Bowden, Peter Topping und Paul Linford Integrierte zerstörungsfreie Surveys im „Stonehenge-Dreieck" bei Amesbury, Wiltshire, haben eine Reihe von Merkmalen sichtbar gemacht, die einen bedeutenden Einfluss auf die Interpretation des Ortes haben. Darunter sind periglaziale und natürliche topographische Strukturen, einschließlich eines Kreidehügels, die die Entwicklung des Fundplatzes beeinflusst haben mögen. Einige geophysikalische Anomalien ähneln den Pfostenlöchern aus dem Bereich des Parkplatzes, die ins Mesolithikum datieren, während andere unter den Hügeln im Westen vielleicht auf Aktivitäten verweisen, die zeitgleich mit Stonehenge selbst sind. Es werden auch Hinweise vorgelegt, dass der „North Barrow" früher innerhalb der akzeptierten Sequenz datiert, und der Unterschied zwischen den östlichen und westlichen Teilen des Umfassungsgrabens wird herausgestellt. Zudem werden neue Daten in Bezug auf die Y- und Z-Löcher und auf die Existenz innerer Wälle, die deren jeweilige Kreisbahnen spiegeln, kurz behandelt. RESUMEN: Prospecciones analíticas de Stonehenge y su entorno inmediato, 2009-2013: parte 1 –el paisaje y las excavaciones, por David Field, Neil Linford, Martyn Barber, Hugo Anderson-Whymark, Mark Bowden, Peter Topping y Paul Linford Las prospecciones integrales no invasivas en el "triángulo" de Stonehenge, Amesbury, Wiltshire, han revelado numerosos rasgos significativos para la interpretación del sitio. Entre ellos existen estructuras periglaciales y topográficas naturales, incluyendo un montículo de creta que podría haber tenido influencia en el desarrollo posterior del sitio. Algunas anomalías geofísicas son similares a los agujeros de poste de cronología mesolítica documentados en el parking, mientras que otros documentados bajo los túmulos del oeste podrían indicar una actividad contemporánea al propio Stonehenge. Se presentan evidencias de que el "túmulo del norte" podría ser más antiguo que lo considerado en la secuencia aceptada y se destacan las diferencias entre las zonas este y oeste de la zanja del cercado, mientras que nuevos datos de los hoyos Y y Z; y la presencia de bancadas internas permiten delimitar sus respectivos circuitos.